Phytochemical and Antimicrobial Activities of Two New Novel Bioactive Analogues of Subergorgic Acid from Subergorgia suberosa - Damodar Reddy, G.; Rama Sekhara Reddy, D.; Razzack, A.; Balaji, K. (Asian Journal of Chemistry, 2010)
A series of bioactive analogues were synthesized from subergorgic acid 1, a cardiotoxic marine metabolite. Two new compounds, 2 and 7 have been synthesized in high yields by the NaBH4 reduction of subergorgic acid 1 and its methyl ester 6, respectively. The structures of new compounds have been determined by spectroscopic methods. The reductions have given the known compounds 3 and 4 as minor products. All these compounds 1, 2, 4, 6 and 7 showed a significant level of antifungal properties.